Peningkatan Kemampuan Berinteraksi Melalui Role Playing Anak Retardasi Mental Di Slb Negeri Surakarta - Kliwon Kliwon; Lia Ratih Nurhidayah (Poltekkes Kemenkes Surakarta, 2019)
Background: The research purpose was determined the implementation of role playing to improve interaction ability of mental retardation students in SLB Negeri Surakarta. The researc was used quasi experiment with one group pre and posttest design. The research was conducted in SLB Negeri Surakarta on February 2018 to January 2019. Data collection method were used observation and interview. Methods: Research method was used role playing through the lecture, discussion, task, and direct practice. Data analysis technique was used bivarian analysis. Results: The research results were shown that the implementation of role playing able to improve the interaction ability of retardation students in SLB Negeri Surakarta. Conclusion: Have significant effect on interaction ability of retardation students in SLB Negeri Surakarta.